TEMA KELANGSUNGAN HIDUP DALAM CERITA PENDEK THE SHAWL KARYA CYNTHIA OZICK - Kembuan, Gian Naldy (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This research entitled â€œTema Kelangsungan Hidup Dalam Cerita Pendek The ShawlÂ  Karya Cyntihia Ozickâ€œ is written to fulfill the requirement of finishÂ  S1 degree in English Department Faculty of Letter Sam Ratulangi University. The Objective of this research based on the problems, the writer simply aims at identify, analyze and describe the survival theme in short story â€œThe Shawlâ€. In analyzing the data the writer uses descriptive Intrinsic and Extrinsic Approach to analyze each of its elements based on some theories such as : Abrams M. H. (1976). The Miror and the Lamp, Stanton R. (1965). An Introduction to Fiction, also from several literature experts. The results of this research, showing that human need much to learn and deeply understanding about â€œSurvivalâ€ in reality, for there are many connections between this matter and the daily life which is proven in some basic human activities such as primary needs of food, clothes, shelters, and rights that will never being apart from this standard game of life called â€œSurvivalâ€ _________________ Keywords: Survival, Short Story The Shawl